The Impact of Engagement-Based Leadership, HR Technology Adaptation, and Skill Development on Work Efficiency: Mediating Through Employee Well-being - Salamatun Asakdiyah; Ajeng Andriani Hapsari (Takaza Innovatix Labs Ltd., 2023)
In the evolving landscape of organizational dynamics, this article investigates the interconnected factors of engagement-based leadership, HR technology adaptation, skill development, and employee well-being within the specific organizational context of PT Nusa Satu Inti Artha (DOKU) in Yogyakarta. Employing a research methodology involving a Random Sampling technique and Structural Equation Modeling with SmartPLS software, the study explores the relationships among these variables and their collective impact on work efficiency at DOKU. The findings highlight the significant influence of engagement-based leadership and HR technology adaptation on both employee well-being and work efficiency. The study provides nuanced insights into the role of skill development and its limited direct impact on work efficiency within this context. Moreover, it uncovers the mediating role of employee well-being, emphasizing its crucial link to leadership practices, technological adaptation, and overall work efficiency. This research contributes tailored recommendations to inform organizational strategies, offering practical insights for fostering a positive, adaptive, and employee-centric work environment at PT Nusa Satu Inti Artha (DOKU) in Yogyakarta.